Dare to light : how to explain a light bulb - Vihalem, Johanna-Mai (My University, 2012)
This diploma work documents the establishment of Dare to Light as an education brand, created in 2010 with an aim to help creative professionals effectively see and accept lighting as part of their art, work and life. The performance piece Light Up Your Life is a roundup of our first revelations while researching the problems of communicating technical information to creative minds. It is based on the observations done while creating a series of lighting design workshops for non-technical professionals. The show is a technical theatre performance in a festival format – extremely portable, with a duration of one hour, targeting theatre professionals but entertaining enough for a anyone to enjoy. The show evolved into a comedy piece about the everyday conflicts in a theatre environment that a lighting designer might experience in their work life, accompanied by the presentation of the main workshop topics conducted during our first year with Dare to Light.
Keywords: Stage lighting.; valosuunnittelu; ljussättning; fi=valosuunnittelu|sv=ljusdesign|en=Lighting Design|